The automotive body volume II: system design - Morello, Lorenzo (Mechanical engineering series, 2011)
The Automotive Body consists of two volumes. The first volume produced the needful cultural background on the body; it described the body and its components in use on most kinds of cars and industrial vehicles: the quantity of drawings that are presented allows the reader to familiarize with the design features and to understand functions, design motivations and fabrication feasibility, in view of the existing production processes. The purpose of this second volume is to explain the links which exist between satisfying the needs of the customer (either driver or passenger) and the specifications for vehicle design, and between the specifications for vehicle system and components. For this study a complete vehicle system must be considered, including, according to the nature of functions that will be discussed, more component classes than considered in Volume I, and, sometimes, also part of the chassis and the powertrain. These two books about the vehicle body may be added to those about the chassis and are part of a series sponsored by ATA (the Italian automotive engineers association) on the subject of automotive engineering; they follow the first book, published in 2005 in Italian only, about automotive transmission. They cover automotive engineering from every aspect and are the result of a five-year collaboration between the Polytechnical University of Turin and the University of Naples on automotive engineering.